(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
This paper deals with long-term stability prediction and monitoring methods by room-and-pillar mining system. Roof-to-floor convergence and conditional thickness methods suit for calculations. They allow determination of the location, area and time of the collapse in a mining block. The uncertainty in time is less than 10 % at the 95 % confidence level. Roof-to-floor convergence method is preferred; it takes into consideration all the geological and mining feature in the critical area. Conditional thickness method demands supplementary investigations, determination of the influence factors on the process. The applicability of these methods is clearly demonstrated.